Editorial jornalístico : uma análise do mandato de Eduardo Cunha à frente da Presidência da Câmara sob a ótica de três jornais brasileiros - Rodrigues, Juliano Oliveira (2018)
From the influence of sociopolitical processes in journalistic routines, the research intends to verify how three Brazilian newspapers have positioned themselves in their editorials during the period in which the former Federal Deputy Eduardo Cunha (PMDB-RJ) presided over the Federal Chamber. This will be done through the analysis of nine editorials of O Estado de S.Paulo, O Globo and Zero Hora newspapers, three of each. The research focuses on the editorials of the periodicals from three pre-established time-cuts and that were remarkable for the trajectory of the parliamentarian. The following moments were chosen: election to the presidency of the Chamber and break with the Dilma Rousseff government, denunciation to the Federal Supreme Court (STF) and impeachment of President Dilma, initiation of Cunha’s cassation process and his removal by judicial decision. The method used is Thompson's Depth Hermeneutics. The technique is the discursive analysis of Patrick Charaudeau. In a first step, it is made explicit the methodological strategies and a bibliographical revision on the journalism and the editorial genre. Then, the analysis is performed from its three moments: socio-historical analysis, discursive analysis and interpretation and reinterpretation. The conclusion is that there was a strong transformation in the editorial discourse of journalistic companies that make up the corpus, through the influence of the political context of the time and the very identity of each of the publications.